Application of stochastic model in field of engineering: monte carlo method in modeling fatigue crack propagation / F.R.M Romlay - Romlay, F.R.M (2006)
This paper deals with the modeling of fatigue crack propagation on a gear tooth using a dual boundary element method. The effects of life cycle to the multiple site fatigue crack propagation were studied. Analysis of stress intensity factor was performed by the deterministic approach using a dual boundary element method. The dual boundary element method was used to simplify the crack model through the numerical approach. The complex problems have been solved using the information from a boundary condition only. Next, the initial crack and life cycle of the structure have been predicted using stochastic method which is Monte Carlo. The crack size and fatigue life were computed until failure of the structure. The failure analysis was performed by a linear elastic fracture mechanics. The scenarios of the fatigue crack propagation were given by all integration of both dual boundary element and Monte Carlo method. Therefore. fatigue life of multiple site crack structure can be predicted.